Project-Based Learning (PBL) Method in Arabic Language Learning to Develop Students' Literacy Skills - Luhulima, Yusuf Abdurrachman (JURNAL IJ-ATL, 2024)
This study aims to analyze the application of the Project-Based Learning (PBL) method in Arabic language learning to develop students' literacy skills. PBL is applied as an innovative approach that encourages students to actively learn through relevant and contextual projects. This study uses a qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the application of PBL improves literacy skills, such as reading, writing, speaking, and listening in Arabic while motivating students to learn collaboratively and creatively. PBL also helps students develop 21st-century skills, such as problem-solving and critical thinking. However, this study has limitations in terms of sample coverage and duration of implementation. Therefore, further research is recommended to expand the scope and explore the integration of technology in PBL. The contribution of this study is to provide new insights into the application of PBL in the context of Arabic language learning to improve students' literacy skills as a whole.